The effectiveness of providing peer benchmarked feedback to hip replacement surgeons based on patient-reported outcome measures—results from the PROFILE (Patient-Reported Outcomes: Feedback Interpretation and Learning Experiment) trial: a cluster randomised controlled study. Issue 7 (31st July 2015) - Boyce, Maria B; Browne, John P
Abstract : Objective: To test whether providing surgeons with peer benchmarked feedback about patient-reported outcomes is effective in improving patient outcomes. Design: Cluster randomised controlled trial. Setting: Secondary care—Ireland. Participants: Surgeons were recruited through the Irish Institute of Trauma and Orthopaedic Surgery, and patients were recruited in hospitals prior to surgery. We randomly allocated 21 surgeons and 550 patients. Intervention: Surgeons in the intervention group received peer benchmarked patient-reported outcome measures (PROMs) feedback and education. Main outcome variable: Postoperative Oxford Hip Score (OHS). Results: Primary outcome data were available for 11 intervention surgeons with responsibility for 230 patients and 10 control surgeons with responsibility for 228 patients. The mean postoperative OHS for the intervention group was 40.8 (95% CI 39.8 to 41.7) and for the control group was 41.9 (95% CI 41.1 to 42.7). The adjusted effect estimate was −1.1 (95% CI −2.4 to 0.2, p=0.09). Secondary outcomes were the Hip Osteoarthritis Outcome Score (HOOS), EQ-5D and the proportion of patients reporting a problem after surgery. The mean postoperative HOOS for the intervention group was 36.2 and for the control group was 37.1. The adjusted effect estimate was −1.1 (95% CI −2.4 to 0.3, p=0.1). The mean postoperative EQ-5D for the intervention group was 0.85 and for the control group was 0.87. The adjusted effect estimate was −0.02 (95% CI −0.05 to 0.008, p=0.2). 27% of intervention patients and 24% of control patients reported at least one complication after surgery (adjusted OR=1.2, 95% CI 0.6 to 2.3, p=0.6). Conclusions: Outcomes for patients operated on by surgeons who had received peer benchmarked PROMs data were not statistically different from the outcomes of patients operated on by surgeons who did not receive feedback. PROMs information alone seems to be insufficient to identify opportunities for quality improvement. Trial registration number: ISRCTN 69032522.